Molecular identification and activity upon chromogenic substrates of a venombin A from Bothrops atrox Peruvian snake venom - Sandoval, Gustavo A. (2010)
n this work, the thrombin-like enzyme (TLE) from Bothrops atrox has been identified by mass spectrometry and its enzymatic activity evaluated upon several synthetic substrates. The enzyme was purified to homogeneity using three chromatography steps on Sephadex G-75, CM-Sephadex C-50 and Agarose-PAB. Also, molecular weight by PAGE-SDS was determined. For molecular identification of this enzyme, mass spectrometry-based peptide mass fingerprinting was used and later in silico analysis. Enzymatic activities were determined using bovine fibrinogen, BApNA and also upon specific chromogenic substrates such as S-2238, S-2251 y S-2266. As a result of these biochemical and structural procedures, we obtained a TLE from B. atrox venom with a molecular weight of 29,6 kDa. Mass spectrometry analysis of obtained peptides, allow us to identify this enzyme as a venombin A, showing a 75% sequence homology. After recording enzymatic activity, this TLE showed coagulant activity on bovine fibrinogen and upon BApNA, S-2238 y S-2266, being unable to hydrolyze S-2251 substrate. Using this combination of structural and functional approaches, we have identified the main component of B. atrox venom related to its coagulant activity, as well as a detailed evaluation of its enzymatic activity upon several substrates